2022
DOI: 10.3389/fcell.2022.954431
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNAs-derived small RNAs and their application potential in multiple diseases

Abstract: The role of tRNAs is best known as adapter components of translational machinery. According to the central dogma of molecular biology, DNA is transcribed to RNA and in turn is translated into proteins, in which tRNA outstands by its role of the cellular courier. Recent studies have led to the revision of the canonical function of transfer RNAs (tRNAs), which indicates that tRNAs also serve as a source for short non-coding RNAs called tRNA-derived small RNAs (tsRNAs). tsRNAs play key roles in cellular processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 155 publications
0
8
0
Order By: Relevance
“…Most recently, this list of non-canonical functions has expanded due to the discoveries of tRNA fragments that serve numerous unanticipated roles in biology. The rapid pace of the discoveries and the important roles of the tRNA fragments in gene expression, development, and health have been summarized in numerous excellent review articles (Anderson and Ivanov 2014;Kumar et al 2016;Oberbauer and Schaefer 2018;Guzzi and Bellodi 2020;Kim et al 2020;Xie et al 2020;Chu et al 2022;George et al 2022;Hou et al 2022;Pekarsky et al 2022). We direct the reader to these reviews regarding the roles of tRNA fragments in development, health and disease.…”
Section: Trna Fragments and Regulation Of Gene Expressionmentioning
confidence: 99%
“…Most recently, this list of non-canonical functions has expanded due to the discoveries of tRNA fragments that serve numerous unanticipated roles in biology. The rapid pace of the discoveries and the important roles of the tRNA fragments in gene expression, development, and health have been summarized in numerous excellent review articles (Anderson and Ivanov 2014;Kumar et al 2016;Oberbauer and Schaefer 2018;Guzzi and Bellodi 2020;Kim et al 2020;Xie et al 2020;Chu et al 2022;George et al 2022;Hou et al 2022;Pekarsky et al 2022). We direct the reader to these reviews regarding the roles of tRNA fragments in development, health and disease.…”
Section: Trna Fragments and Regulation Of Gene Expressionmentioning
confidence: 99%
“…LeuCAG3 tsRNA can promote hepatocellular carcinogenesis by binding to two ribosomal protein mRNAs (RPS28 and RPS15) to enhance their translation [16]. Likewise, previous studies have also identified multiple tRFs involved in various aspects of prostate cancer [17]. tRNA-halves (also called SHOT-RNAs) from tRNA Asp-GUC , tRNA His-GUG , and tRNA Lys-CUU have been noted as promoters of cellular proliferation in breast cancer and PRAD in a sex hormone-dependent manner [18].…”
Section: Introductionmentioning
confidence: 91%
“…tRF-5 can be generated by Dicer cleaving the D-loop, D stem, or 5’ half of the anticodon stem of mature tRNAs. According to its different cleavage sites, tRF-5 can be categorized into three specific subtypes: (1) tRF-5a (14–16 nt); (2) tRF-5b (22–24 nt); (3) tRF-5c (28–30 nt) [ 58 ]. tRF-2 and i-tRF are recently discovered atypical tsRNAs derived from tRNAs, produced by nuclear-encoded and mitochondrial-encoded tRNAs, present in different tissues and individuals [ 56 , 59 ].…”
Section: Discovery Biogenesis and Regulatory Mechanism Of Tsrnasmentioning
confidence: 99%